THE INFLUENCE OF FAMILY ECONOMIC EDUCATION, SELF-CONTROL, AND INDIVIDUAL MODERNITY ON CONSUMPTIVE BEHAVIOR THROUGH FINANCIAL LITERACY IN BACHELOR STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS NEGERI MALANG CLASS OF 2020 - Arista Elok Dwi Rangga; Agung Haryono; Sugeng Hadi Utomo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The purpose of this study was to determine the effect of family economics education, self-control, and individual modernity on consumptive behavior through financial literacy in undergraduate students of the Faculty of Economics and Business, State University of Malang, class of 2020. This research is included in a quantitative approach using the explanatory method. Data collection used a questionnaire that was distributed to 291 students. Data analysis used Structural Equation Modeling (SEM) in the LISREL program. The results of the analysis test in this study indicate that family economic education, self-control, and individual modernity influence consumptive behavior through financial literacy.